Analisis Determinan Permintaan Kredit Modal Kerja Terhadap Bank Umum di Yogyakarta - Indrawahyu, May Leny; Khoirudin, Rifki; Suripto, Suripto (GEMA EKONOMI, 2023)
The purpose of this study was to determine the factor that influences of the demand for working capital loans at commercial banks in Yogyakarta. The variable used in this study is the dependent variable, namely the amount of demand for working capital credit. In contrast, the independent variable is the interest rate for working capital credit, economic growth, per capita income, and savings. This study uses data analysis methods: multiple linear regression analysis, classical assumption test, and hypothesis testing. The data in this study uses secondary data from Bank Indonesia (www.bi.go.id), the Financial Services Authority (www.ojk.go.id), the Central Bureau of Statistics (www.bps.go.id), and BAPPEDA. The results of the analysis in this study simultaneously variable working capital credit interest rates, economic growth, income per capita, and Dpk affect the amount of working capital credit. The interest rate variable for working capital credit is not significant to the amounts of working capital credit. The economic growth variable is insignificant to the working capital credit amount. The income per capita variable is not significant to the amount of working capital credit. The Third Party Funds (TPF) variable is significant to the total demand for working capital loans